MENGENAL TEORI KOGNITIF SOSIAL ALBERT BANDURA DAN IMPLIKASINYA DALAM DUNIA PENDIDIKAN - Emanuel Haru (STIPAS St. Sirilus Ruteng, 2016)
Talking about education never be separated from terminology of education psychology. One of theories in relation with this topic is beaviorism learning theory.The beaviorism concept is elaborated by Albert Bandura in social cognitive theory.For him,most ofhuman learning occurs in social environment. In contacting with others, the man gets the knowledges, rules, skills, strategies, convictions and attitudes. At the same time,the man also sees the models, by those they will learn the advantage, conformity and the results of those behaviours. So, individuals act upon their convictions about their capabilities and the expected results from their acts. In this writing, Emanuel Haru will go further in presenting some constucts of social cognitive theory of Albert Bandura. The way of learning concept, modeling process, its effect on learning and performance, goal and expectation, self eficacy and the application of learning theory in education realm.